Iconic gestures prime words: comparison of priming effects when gestures are presented alone and when they are accompanying speech - So, Wing Chee; Low, Alvan; Yap, De Fu; Kheng, Eugene; Yap, Melvin (Frontiers in Psychology, 2013)
Previous studies have shown that iconic gestures presented in an isolated manner prime visually presented semantically related words. Since gestures and speech are almost always produced together, this study examined whether iconic gestures accompanying speech would prime words and compared the priming effect of iconic gestures with speech to that of iconic gestures presented alone. Adult participants (N = 180) were randomly assigned to one of three conditions in a lexical decision task: Gestures-Only (the primes were iconic gestures presented alone); Speech-Only (the primes were auditory tokens conveying the same meaning as the iconic gestures); Gestures-Accompanying-Speech (the primes were the simultaneous coupling of iconic gestures and their corresponding auditory tokens). Our findings revealed significant priming effects in all three conditions. However, the priming effect in the Gestures-Accompanying-Speech condition was comparable to that in the Speech-Only condition and was significantly weaker than that in the Gestures-Only condition, suggesting that the facilitatory effect of iconic gestures accompanying speech may be constrained by the level of language processing required in the lexical decision task where linguistic processing of words forms is more dominant than semantic processing. Hence, the priming effect afforded by the co-speech iconic gestures was weakened.